2011
DOI: 10.1016/j.cmet.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inorganic Nitrate Improves Mitochondrial Efficiency in Humans

Abstract: Nitrate, an inorganic anion abundant in vegetables, is converted in vivo to bioactive nitrogen oxides including NO. We recently demonstrated that dietary nitrate reduces oxygen cost during physical exercise, but the mechanism remains unknown. In a double-blind crossover trial we studied the effects of a dietary intervention with inorganic nitrate on basal mitochondrial function and whole-body oxygen consumption in healthy volunteers. Skeletal muscle mitochondria harvested after nitrate supplementation displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
621
19
20

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 595 publications
(701 citation statements)
references
References 167 publications
41
621
19
20
Order By: Relevance
“…These findings are in line with most previous investigations [4,5,22,37], and similar to the results of a recent meta-analysis [6]. The physiological mechanisms underlying the decreased V O2 subsequent to nitrate supplementation have not been fully elucidated, but may be accounted for by: a) an improvement in the efficiency of mitochondrial respiration [35] and/or b) enhanced efficiency of muscle force production [7].…”
Section: Effect Of Nitrate Supplementation On Cardiorespiratory Variasupporting
confidence: 91%
See 3 more Smart Citations
“…These findings are in line with most previous investigations [4,5,22,37], and similar to the results of a recent meta-analysis [6]. The physiological mechanisms underlying the decreased V O2 subsequent to nitrate supplementation have not been fully elucidated, but may be accounted for by: a) an improvement in the efficiency of mitochondrial respiration [35] and/or b) enhanced efficiency of muscle force production [7].…”
Section: Effect Of Nitrate Supplementation On Cardiorespiratory Variasupporting
confidence: 91%
“…Tissue oxygenation in the vastus lateralis was also elevated following nitrate supplementation in that study. These findings are supportive of the notion that nitrate supplementation may reduce muscle O2 consumption during exercise in hypoxia, presumably via the aforementioned mitochondrial [35] and/or muscle [7] alterations that also manifest as a reduced V O2. Interestingly, Arnold et al [38] found that runners identified as 'responders' to nitrate supplementation during a 10,000 m TT in moderate hypoxia (FIO2 15.4 %) typically experienced a lower SaO2 during the placebo TT than 'non-responders' (82 vs 84 %).…”
Section: Effect Of Nitrate Supplementation On Cardiorespiratory Variasupporting
confidence: 82%
See 2 more Smart Citations
“…The Karolinska group showed in a double‐blind crossover trial in healthy volunteers that oral inorganic nitrate supplementation improves oxidative phosphorylation efficiency in skeletal muscle mitochondria. An analysis of mitochondrial function revealed decreased expression of ANT and decreased mitochondrial membrane uncoupling (Larsen et al ., 2011). It has also been proposed that under hypoxic conditions, nitrite may act as the terminal electron acceptor in place of oxygen (Basu et al ., 2008).…”
Section: A Novel Therapeutic Pathway: Nitrate–nitrite–nomentioning
confidence: 99%